Childhood Socioeconomic Status Does Not Predict Late-Life Cognitive Decline in the 1936 Lothian Birth Cohort - Racine Maurice, Stéphanie; Hébert, Alisone; Turcotte, Valérie; Potvin, Olivier; Hudon, Carol; Duchesne, Simon (Frontiers in Psychology, 2021)
This study examined childhood socioeconomic status (SES) as a predictor of later-life cognitive decline. Data came from 519 participants in the Lothian Birth Cohort 1936 (LBC1936) study. Measures at 11 years of age included parents’ educational attainment, father’s occupational status, household characteristics, and a composite measure of global childhood SES (i.e., a total of low SES childhood indicators). Cognitive abilities were assessed by the Mini-Mental State Exam at ages 69.8, 72.8, and 76.7 years. Most indicators of low childhood SES (i.e., father manual worker, less than secondary school father education, household overcrowding, exterior located toilet, and global childhood SES) did not predict cognitive decline between the ages of 69.8 and 76.7. Participants with less educated mothers showed an increase in cognitive decline (β = -0.132, p = 0.048, CI = -0.80, -0.00). The relationship between maternal educational attainment and cognitive decline became non-significant when controlling for adult SES (i.e., participant educational attainment and occupation). Adult SES did not mediate the latter relationship. This study provides new evidence that childhood SES alone is not strongly associated with cognitive decline. New knowledge is critical to improving population health by identifying life span stages in which interventions might be effective in preventing cognitive decline.